Rural land system reforms in China: History, issues, measures and prospects - Zhou, Yang; Li, Xunhuan; Liu, Yansui (Land use policy, 2020)
•We systematically reviewed the process, problems, measures and prospects of land system reform in China.•China's rural reform originated from its rural land system reform, and even the latter leads and promotes to the former to a certain extent.•China's land system reform can be roughly divided into five stages since 1949, and is now entering a period of deepening reform.•Land system reform can promote optimal allocation of resources, revitalize rural economy and coordinate human-land relationship. Land system reform (LSR) helps to protect farmers' rights and interests and national food security. China is a country dominated by agriculture but insufficient arable land resources. The contradiction between man and land is prominent. To alleviate the man-land contradiction, the Chinese government has carried out a series of LSRs, especially in the past half century. Extensive and in-depth studies have been done on the process and stage characteristics of China's LSRs, but the systematic analysis on the necessity, problems and key measures to deepen the land system reform is still insufficient. Based on a systematic review of the history of the evolution of China's LSRs, this study firstly analyzed the key issues and new challenges existing in or arising from China's land system, then put forward the necessity of deepening the reform of land system, and discussed specific measures taken to deepen the reform of land system in China at present and finally pointed out the future LSR’s direction. The results show that China's rural LSR has gone through five stages in general since 1949. The key problems existing or arising from the current land system in China include unclear subject of land property right, serious inefficient utilization of land resources, rapid farmland conversion and conflict between farmers’ interests and land system. The dual land system in urban and rural areas has severely restricted the integration of social and economic development in this country. The Chinese government is actively promoting the reforms of rural agricultural land, collective operating construction land and homestead to further remove the dual institutional barriers that hinder the establishment of an integrated land trading market. The vision is good, but there is still a long way to go for China's LSR. The direction of China's rural LSR is to make the property rights relationship clearer, the farmland rights more complete, the transfer transactions more market-oriented and the property rights’ protection more equal. Deepening the rural LSRs is helpful to improve the efficiency of land resource utilization, safeguard the rights and interests of farmers, promote the coordination of human-land relationship, and inject new vitality and momentum into rural revitalization. Cooperative promotion of land resource capitalization reform and household registration system reform is the key area of land system reform in China in the future.